No Evidence to Favor 99mTc-HMPAO or 99mTc-ECD for Ictal Brain Perfusion SPECT for Identification of the Seizure Onset Zone. (November 2021) - Jaber, Mariam; Taherpour, Jila; Voges, Berthold; Apostolova, Ivayla; Sauvigny, Thomas; House, Patrick M.; Lanz, Michael; Lindenau, Matthias; Klutmann, Susanne; Martens, Tobias; Stodieck, Stefan; Buchert, Ralph
Abstract : Purpose: Ictal brain perfusion SPECT with the tracer 99m Tc-HMPAO or 99m Tc-ECD is widely used for identification of the epileptic seizure onset zone (SOZ) in presurgical evaluation if standard pointers are uncertain or inconsistent. For both tracers, there are theoretical arguments to favor it over the other for this task. The aim of this study was to compare the performance of ictal brain perfusion SPECT between 99m Tc-HMPAO and 99m Tc-ECD in a rather large patient sample. Patients and Methods: The study retrospectively included 196 patients from clinical routine in whom ictal perfusion SPECT had been performed with stabilized 99m Tc-HMPAO (n = 110) or 99m Tc-ECD (n = 86). Lateralization and localization of the SOZ were obtained by the consensus of 2 independent readers based on visual inspection of the SPECT images. Results: The 99m Tc-HMPAO group and the 99m Tc-ECD group were well matched with respect to age, sex, age at first seizure, duration of disease, seizure frequency, history of previous brain surgery, and findings of presurgical MRI. The proportion of lateralizing ictal SPECT did not differ significantly between 99m Tc-HMPAO and 99m Tc-ECD (65.5% vs 72.1%, P = 0.36). Sensitivity of ictal perfusion SPECT (independent of the tracer) for correct localization of the SOZ in 62 patients with temporal lobe epilepsy and at least worthwhile improvement (Engel scale ⩽ III) 12 months after temporal epilepsy surgery was 63%. Conclusions: This study does not provide evidence to favor 99m Tc-HMPAO or 99m Tc-ECD for identification of the SOZ by ictal perfusion SPECT.